Minimum Activation Power of a Passive UHF RFID Tags: a Low Cost Method - Samuel Bloch da Silva; Anderson Ribeiro Correia (Journal of Aerospace Technology and Management, 2018)
RFID is an automatic contactless identifi cation method based on radio frequency (RF). The reading process depends of the power of electromagnetic signal received by a tag. Thus an accurate characterization of RFID tags is crucial for early adopter in aerospace industry. The present study shows the preliminary approach to characterize the reading distance for UHF RFID passive tag from the low-cost application test deployment.